Spectroscopic investigations of Nd3+doped gadolinium calcium silica borate glasses for the NIR emission at 1059 nm - C. R. Kesavulu (2018)
© 2016 Elsevier B.V. The Nd3+-doped gadolinium calcium silica borate (BSGdCaNd) glasses of composition (55-x) B2O3- 10 SiO2- 25 Gd2O3-10 CaO -x Nd2O3, where x = 0.0, 0.05, 0.5, 1.0, 1.5, 2.0 and 2.5 mol %, have been prepared by conventional melt quenching technique and are characterized through structural, thermal, absorption, emission and decay time measurements. Based on the Judd-Ofelt intensity parameters and radiative properties were determined from the absorption spectrum. The emission spectra recorded for BSGdCaNd glasses gives three emission transitions4F3/2 → 4I9/2(903 nm),4F3/2 → 4I11/2(1059 nm) and4F3/2 → 4I13/2(1334 nm) for which effective bandwidths (Δλeff) and stimulated emission cross-section (σ(λp)) are evaluated. Branching ratios (βR) measured for BSGdCaNd0.5 glass show that4F3/2 → 4I11/2transition is quite suitable for lasing applications. The intensity of emission spectra increases with increase in the concentration of Nd3+ion up to 1.0 mol% and beyond that concentration, quenching is observed. The decay from4F3/2level is found to be non-exponential nature for concentrations of Nd3+ions. The non-exponential curve has been fitted to the Inokuti-Hirayama model to understand the nature of energy transfer process. Hence, the high emission cross-section (1.39 × 10−20 cm2), branching ratio (0.58) and long lifetime (342 μs) indicate that the BSGdCaNd0.5 glass system could be considered as a good candidate for strong NIR lasers at 1059 nm.